The effects of the environment and affective factors towards reading achievement of year five pupils in two schools in the district of Johor Bahru, Johor Darul Ta'zim - 422032 Normah Othman (Skudai : UTM, 1999)
Project Paper (Bachelor of Science with Education (TESL)) - Universiti Teknologi Malaysia, 1999